Agronomical and Economic Evaluation of Different Soil Cultivation Systems - Sulyok, Dénes (Acta Agraria Debreceniensis, 2006)
In the interest of profitable plant production and environmental protection we have to make an effort to protect and improve the productivity of our soils while moderating production limiting factors. Due to different soil cultivation methods, the quantity of yield and required expenses also differ. We examined the production costs in four different production technology systems. Overall, it can be said that farming standards are good, since cost prices were low (2001: 14-15 HUF/kg, 2002: 15-21 HUF/kg, 2003: 39-49 HUF/kg) in the case of all main products per 1 kg. Cost prices were lowest in the case of direct sowing, probably due to low machinery costs. All economic indicators have to be compared when choosing the most suitable production technology in a specific farming environment.